Apache legends & lore of southern New Mexico : from the sacred mountain - Sanchez, Lynda; Bigmouth, Percy 1891-1959 (Charleston, SC History Press, 2014)
Storytelling has been a vital and vivid tradition in Apache life. Coyote tales, the creation legend and stories of historic battles with Comanche and Anglo intruders create a colorful mosaic of tribal heritage.
Foreword, by Mary M. Serna -- Acknowledgements -- Introduction: Coming full circle -- In the shadow of the sacred mountain -- History and traditions of the Apache -- The legacy of Old Scout Bigmouth (1855-1958) -- Percy Bigmouth's gifts (1891-1959) -- The coveted haven -- "I kept it in my sleeves" (as told by Percy Bigmouth and Eve Ball) -- The legend of creation -- Its strings are made of rainbows: the Apache cradleboard ceremony -- Classic animal stories and antics -- Old coyote (the trickster) tales -- Of doves and Old Brown Turkey -- Legends of caves and bats -- On the war trail -- Of raiding and war -- Enemy people (Comanches) -- The return of the captives -- The Battle of Coyote Mountain -- victory and bitter defeat -- Apache vengeance -- gold, silver and a pueblo's demise -- Crossing over the bridge.
101873
Keywords: Apache Indians -- New Mexico -- Folklore; Mescalero Indians -- New Mexico -- History; Lipan Indians -- History; Mescalero Indians -- New Mexico -- Folklore; Lipan Indians -- Folklore; Indian mythology